Comprehensive network security approach: security breaches at retail company-a case study - Jahanirad, M.; Yahya, A.L.N.; Noor, R.M. (2012)
The development of the Web technologies and services increases the level of threats to data security in companies and enterprises day by day. As criminals are turn into professional network intruders, new laws and legislations are introduced to cover information security. Even though on-line businesses provide the productivity and efficiency advantages, without the comprehensive network security plan an online retail company which operates with information systems about its daily businesses, increases its risk to become vulnerable to security breaches. The purpose of this article is to introduce a comprehensive network security approach for an online retail company which suffers from security breaches. This article begins with the brief introduction about the problem statement and the proposed method to complete the security enhancement. Next, an ideal network architecture suggested, using both basic network diagram and security enhancement network diagram. The recent task will be continued by implementing the security and password policies to the network. Finally the whole procedure will be simulated and examined using Cisco Packet Tracer Experiment. The simulation results show that the approach was successful in designing a comprehensive network security, and to defend the company against security breaches.